2022
DOI: 10.3390/jof8030279
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy Should Be Reserved as Second-Line Treatment of Onychomycosis: A Systematic Review of Onychomycosis Clinical Trials

Abstract: Onychomycosis is the most common nail disease encountered in clinical practice. Its importance extends well beyond aesthetics, often causing pain, difficulty with ambulation and performing daily activities, and impairing quality of life. Many patients fail to achieve cure with antifungal monotherapy and recurrences are common. Combination therapy has therefore gained considerable interest, given the potential for drug synergy and prevention of antifungal resistance, but it has not been well studied. A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 96 publications
0
16
0
1
Order By: Relevance
“…88 , 89 Combination therapy should not be considered first-line treatment and should be reserved for patients with poor prognostic factors (ie, older age, immunosuppression, mixed infections) or for those who have failed monotherapy for onychomycosis. 91 In a systematic review of race reporting in onychomycosis clinical trials, less than a fifth (17.5%; 32/182) of trials reported on race and/or ethnicity, with only one trial comparing treatment efficacy in different subgroups. 92 Therefore, treatment recommendations garnered from these trials should be interpreted with caution in patients of color.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…88 , 89 Combination therapy should not be considered first-line treatment and should be reserved for patients with poor prognostic factors (ie, older age, immunosuppression, mixed infections) or for those who have failed monotherapy for onychomycosis. 91 In a systematic review of race reporting in onychomycosis clinical trials, less than a fifth (17.5%; 32/182) of trials reported on race and/or ethnicity, with only one trial comparing treatment efficacy in different subgroups. 92 Therefore, treatment recommendations garnered from these trials should be interpreted with caution in patients of color.…”
Section: Treatmentmentioning
confidence: 99%
“…195 However, it is not well studied and standardized treatment regimens have not been established. In a systematic review of 30 onychomycosis clinical or randomized controlled trials [15 medication only studies, 15 medication and procedural (laser, debridement, PDT) studies], 91 significant clinical benefit of medication combination therapy vs monotherapy was observed in more than half (60%) of studies. However, trials were not robustly designed and lacked sufficient follow-up compared to pivotal monotherapy trials.…”
Section: Combination Treatmentsmentioning
confidence: 99%
“…The survey results indicated that combination therapy with both topical and oral antifungals or an oral antifungal alone was used in 70% of cases in which >50% of the nail was affected or the nail matrix was involved. 1 Gregoriou also presented the results of a systematic review evaluating combination therapies of oral and topical medications or medications and procedures versus monotherapy, 3 which revealed that use of combination therapy led to a "significant clinical benefit" in 60% of cases. The review revealed that mycological cure rates were significantly higher when oral terbinafine and topical amorolfine were used in conjunction compared with oral terbinafine alone, whereas the combination of oral griseofulvin and topical tioconazole showed significantly higher complete cure rates, mycological cure rates, and lower relapse rates compared with griseofulvin oral monotherapy.…”
Section: Combination Treatment Updatesmentioning
confidence: 99%
“…The review revealed that mycological cure rates were significantly higher when oral terbinafine and topical amorolfine were used in conjunction compared with oral terbinafine alone, whereas the combination of oral griseofulvin and topical tioconazole showed significantly higher complete cure rates, mycological cure rates, and lower relapse rates compared with griseofulvin oral monotherapy. 3 However, other combination studies evaluated, including oral itraconazole and topical amorolfine, revealed contradictory results. 3 Combining medication with a procedure such as debridement or laser therapy also led to a significant clinical benefit in 93.3% of studies when compared with medical monotherapy alone.…”
Section: Combination Treatment Updatesmentioning
confidence: 99%
See 1 more Smart Citation